Biochemical Properties and Potential Application of Proteases from Alkalophilic Bacillus lehensis G1 - Noorul Aini Sulaiman,; Nor Muhammad Mahadi,; Nur Zazarina Ramly, (Tropical Life Sciences Research, 2019)
The biochemical properties of extracellular proteases enzymes from Malaysia Alkalophilic’s bacteria, Bacillus lehensis G1, were investigated. The secreted enzymes were tested on 2% of skim milk agar. Results demonstrated that the enzyme could maintain the activity up to 60°C within an extensive range of pH from 3 to 11 with the optimal pH and temperature of 7.0 and 40°C, respectively. The proteases activity were also observed to be increased in the presence of several ions such as Mn2+, Fe2+, Cu2+, Mg2+ and Co2+. Whilst, the enzyme activity was marginally inhibited with the addition of Ca2+, K+ and Ni2+ with the residual activity of 85%, 81%, and 75%, respectively. Furthermore, the extracellular proteases have shown to be compatible with several Malaysia commercial liquid detergents, which could be beneficial for stain removal. The potential application of proteases in gelatine decomposition from used X-ray films was also determined in this article.Pencirian enzim ekstraselular protease daripada bakteria Alkalophilic Bacillus lehensis G1 dari Malaysia telah dikaji. Enzim protease yang dirembeskan diuji pada agar susu skim 2%. Keputusan menunjukkan protease ekstraselular mampu mengekalkan aktiviti sehingga suhu 60°C di dalam julat pH yang luas iaitu 3 hingga 11 dengan suhu optimum pada 40°C dan pH optimum pada 7.0. Aktiviti enzim juga diperhatikan akan meningkat dengan penambahan beberapa ion iaitu Mn2+, Fe2+, Cu2+, Mg2+ dan Co2+. Manakala aktiviti protease didapati sedikit direncat dengan kehadiran ion Ca2+, K+ dan Ni2+ dengan baki aktiviti sebanyak 85%, 81% dan 75%. Protease ekstraselular juga didapati serasi dengan beberapa cecair detergen komersial dari Malaysia, yang menunjukkan protease ini boleh dimanfaatkan sebagai pembersih kotoran pada pakaian. Selain itu, potensi kegunaan protease yang dihasilkan oleh B. lehensis G1 ke atas penguraian gelatin dari filem X-ray yang telah digunakan juga telah dilakukan di dalam kajian ini.